2015
DOI: 10.1039/c5tc02753e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electron mobility in crystalline thionated naphthalene diimides

Abstract: A series of five thionated naphthalene diimides (NDIs) with linear alkyl chains was synthesized and the optoelectronic, self-assembly, and device properties were studied. When tested in organic thin-film transistors, the electron mobilities of the thionated derivatives are three orders of magnitude higher than the non-thionated parent analogue, with the highest mobility measured for cis-S2 (µ max = 7.5 × 10 -2 cm 2 V -1 s -1 ). In contrast to branched chain PDIs and NDIs, the electron mobility does not increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 49 publications
4
68
0
Order By: Relevance
“…15 However, in 2014 in an elegant study Seferos et al discovered that the reaction of PDIs with Lawesson's Reagent resulted in the substitution of the carbonyl oxygens with sulfur to give tetra-thionated PDIs, 16 a strategy that was also employed with naphthalene diimides. 17 It was found that subsequent substitutions resulted in a progressive bathochromic shift in the absorption maxima from 525 nm for the unfunctionalised N,N'-di(3-hexylundecyl)-perylene-3,4:9,10-tetracarboxylic diimide A to 704 nm for the tetra-thionated analogue B. The bathochromic shift in absorbance is accompanied by a shift to more positive potentials for reduction processes.…”
Section: Thionated Perylene Diimides With Intense Absorbance In the Nmentioning
confidence: 99%
“…15 However, in 2014 in an elegant study Seferos et al discovered that the reaction of PDIs with Lawesson's Reagent resulted in the substitution of the carbonyl oxygens with sulfur to give tetra-thionated PDIs, 16 a strategy that was also employed with naphthalene diimides. 17 It was found that subsequent substitutions resulted in a progressive bathochromic shift in the absorption maxima from 525 nm for the unfunctionalised N,N'-di(3-hexylundecyl)-perylene-3,4:9,10-tetracarboxylic diimide A to 704 nm for the tetra-thionated analogue B. The bathochromic shift in absorbance is accompanied by a shift to more positive potentials for reduction processes.…”
Section: Thionated Perylene Diimides With Intense Absorbance In the Nmentioning
confidence: 99%
“…Thionation is a straightforward oxygen–sulfur atomic substitution that remarkably tunes the material's optical and electronic properties without the need to synthesize a new compound from scratch but via a simple and single‐step reaction . Seferos and coworkers demonstrated that perylene diimide small molecules display enhanced charge transport characteristics upon thionation, because of the change in their morphological and photophysical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is assumed that ambient stability of n-type conductivity can be achieved using materials with a LUMO energy level more negative than −3.9 eV. [42][43][44][45][46] The lowering of the LUMO energy of the semiconductor can be obtained by diverse modifications of the electron withdrawing cores such as in naphthalene diimide (NDI) based co-polymers, one of the most studied class of n-type materials [47][48][49][50][51][52][53][54][55] With the core positions being partially blocked in PNDIT2 by the comonomer, the strategy of lowering the LUMO by replacing the imide group by a mono-thioimide group, known as thionation, appears highly suitable for the development of stable n-doped small molecule NDIs [56][57][58][59] and NDI-based polymers. 60,61 Here we make use of thionated PNDIT2, referred to as 2S-trans-PNDIT2 ( Figure 1b) in which two carbonyl oxygens are substituted by sulphur with full trans-regioselectivity.…”
mentioning
confidence: 99%